A Synthetic Approach Reveals Extensive Tunability of Auxin Signaling - Havens, Kyle A.; Guseman, Jessica M.; Jang, Seunghee S.; Pierre-Jerome, Edith; Bolten, Nick; Klavins, Eric; Nemhauser, Jennifer L. (Plant physiology (Bethesda), 2012)
Explaining how the small molecule auxin triggers diverse yet specific responses is a long-standing challenge in plant biology. An essential step in auxin response is the degradation of Auxin/Indole-3-Acetic Acid (Aux/IAA, referred to hereafter as IAA) repressor proteins through interaction with auxin receptors. To systematically characterize diversity in degradation behaviors among IAA ǀ receptor pairs, we engineered auxin-induced degradation of plant IAA proteins in yeast (Saccharomyces cerevisiae). We found that IAA degradation dynamics vary widely, depending on which receptor is present, and are not encoded solely by the degron-containing domain II. To facilitate this and future studies, we identified a mathematical model able to quantitatively describe IAA degradation behavior in a single parameter. Together, our results demonstrate the remarkable tunability conferred by specific configurations of the auxin response pathway.